Kajian Potensi Sosial Budaya dan Strategi Pengembangan Pariwisata Berbasis Rapid Rural Appraisal di Desa Ranupani Kabupaten Lumajang, Jawa Timur - Megasari Noer Fatanti; Desy Santi Rozakiyah; Seli Septiana Pratiwi; Nur Hadi; Luhung A. Perguna; Ahmad Arif Widianto (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
Ranupani Village is administratively located in Senduro District, Lumajang Regency, East Java Province. The naming of Ranupani Village refers to a mountain lake that is very famous among climbers of Mount Semeru, namely Ranu Pani. In addition, there are also two mountain lakes located close to the village area, namely Ranu Regulo and Ranu Kumbolo. Most of the Ranupani Village area is part of the Bromo Tengger Semeru National Park conservation area (TNBTS) so that the landscape condition of Ranupani Village is still maintained. In addition, Ranupani Village is 1 of 10 priority tourism villages developed by the Ministry of Tourism and Creative Industries. As a priority tourist destination, Ranupani Village presents beautiful landscapes and has the potential for a diversity of beliefs (religions) that have been preserved since ancient times. The purpose of this community service activity is to map the natural and social potential of Ranupani Tourism Village to develop community-based tourism. Based on the results of observations and focus group discussions, it was found that the need for strategic efforts that can encourage the participation of residents so that Ranupani Village tourism does not only rely on natural potential but also introduces local wisdom, especially in environmental management and Tengger Tribe customs. In addition, the culinary and souvenir sectors are potentials that can be optimized as the carrying capacity of natural tourism owned by Ranupani Village. Finally, a grand design for developing local community-based tourism is needed by prioritizing cross-sectoral communication and coordination, especially local tourism actors who are the last guard for the future of Ranupani Village.